2006
DOI: 10.1016/j.cmet.2006.03.007
|View full text |Cite
|
Sign up to set email alerts
|

The ratio of phosphatidylcholine to phosphatidylethanolamine influences membrane integrity and steatohepatitis

Abstract: Phosphatidylcholine (PC) and phosphatidylethanolamine (PE) are major phospholipids in mammalian membranes. In liver, PC is synthesized via the choline pathway or by methylation of PE via phosphatidylethanolamine N-methyltransferase (PEMT). Pemt(-/-) mice fed a choline-deficient (CD) diet develop rapid steatohepatitis leading to liver failure. Steatosis is observed in CD mice that lack both PEMT and multiple drug-resistant protein 2 (MDR2), required for PC secretion into bile. We demonstrate that liver failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
547
2
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 618 publications
(585 citation statements)
references
References 47 publications
31
547
2
5
Order By: Relevance
“…PE is also redistributed and exposed to the extracellular environment that signals cell death when the membrane asymmetry is compromised [32]. Li et al described that the decrease in the ratio of PC to PE was associated with a reduction in membrane integrity (Caballero et al2010; [25]). However, a more recent study attributed the loss of membrane integrity to PC deficiency alone [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PE is also redistributed and exposed to the extracellular environment that signals cell death when the membrane asymmetry is compromised [32]. Li et al described that the decrease in the ratio of PC to PE was associated with a reduction in membrane integrity (Caballero et al2010; [25]). However, a more recent study attributed the loss of membrane integrity to PC deficiency alone [31].…”
Section: Discussionmentioning
confidence: 99%
“…It was identified through the two ions found in this group with m/z 750.4191 and 806.4842. In cells, PS is located exclusively in the intracellular environment (Caballero et al), which plays an important role because many intracellular proteins, such as protein kinases, require PS for proper activation and/or location [7,25,31]. Moreover, PS has also been described as a marker of apoptosis [4,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (16) later suggested that a reduction in the PC/PE ratio affects hepatocyte membrane integrity and plays a role in the progression of steatosis to steatohepatitis in humans. Mechanistic Amino acid one-letter code sizes are proportional to amino acid volumes.…”
Section: Resultsmentioning
confidence: 99%
“…This study presents the first structural analysis of a eukaryotic cytidylyltransferase, providing a view into the workings of the active site of the enzyme that controls the rate of phosphatidylcholine synthesis and helps maintain a balanced membrane phospholipid composition (38,48,49). The CCT236 structure, which provides a complete catalytic domain as well as an intimately associated N-terminal extension, expands the repertoire of folds within the nucleotidyltransferase family and reveals unique features that have evolved to bind and position the phosphocholine group.…”
Section: Discussionmentioning
confidence: 99%